A new aspect of serum protein binding of tolbutamide - (:unkn) unknown (My University, 1986)
Tolbutamide is known to bind highly to serum proteins. Quite different values have, however, been reported for binding, ranging from 80 to 99 percent. In this study, in vivo and in vitro binding of increasing concentrations of tolbutamide to human serum proteins were evaluated. In vitro studies were done with serum from three healthy males and for in vivo studies serum samples from eight healthy males who had received 1,000 mg tolbutamide were used. Protein binding was determined by equilibrium dialysis, using DIANORM system. Tolbutamide concentrations were determined by HPLC method of Uihlein and Hack. The results suggest that there is an increase in percent tolbutamide bound with increasing concentrations of tolbutamide. Generally, an inverse relationship between the total concentration of a drug in serum and its bound fraction is observed. Our findings seem to be contrary to this, at least within the concentration range studied. There exists at least two binding sites on albumin with different affinities for tolbutamide and most probably, at low concentrations, the drug binds mainly to the high affinity sites, whereas at higher concentrations additional drug will bind to the lower affinity sites leading to the observed increase in fraction bound with concentration. In conclusion it may be said that serum protein binding is a much more complicated phenomenon than generally stated and that the normal observations are only true for some ideal compounds where only one site of adsorption has to be taken into account.